Ancient worlds a global history of antiquity - Scott, Michael 1981- (Basic Books, 2016)
"Twenty-five-hundred years ago, civilizations around the world entered a revolutionary new era that overturned old order and laid the foundation for our world today. In the face of massive social changes across three continents, radical new forms of government emerged; mighty wars were fought over trade, religion, and ideology; and new faiths were ruthlessly employed to unify vast empires. The histories of Rome and China, Greece and India--the stories of Constantine and Confucius, Qin Shi Huangdi and Hannibal--are here revealed to be interconnected incidents in the midst of a greater drama. In Ancient Worlds, historian Michael Scott presents a gripping narrative of this unique age in human civilization, showing how diverse societies responded to similar pressures and how they influenced one another: through conquest and conversion, through trade in people, goods, and ideas. An ambitious reinvention of our grandest histories, Ancient Worlds reveals new truths about our common human heritage"--Publisher description
"First published in Great Britain by Hutchinson in 2016"--Title page verso
British edition has subtitle: An epic history of East & West
Keywords: Civilization, Ancient; East and West; History, Ancient; Social history / To 500; Social change / History / To 1500; HISTORY / Ancient / General; HISTORY / World; HISTORY / Ancient / Rome; Social change; Social history; To 1500; History